Environmental and Economic Assessment of a Novel Solvolysis-Based Biorefinery Producing Lignin-Derived Marine Biofuel and Cellulosic Ethanol - Svetlana V. Obydenkova; Lucie V. E. Defauw; Panos D. Kouris; David M. J. Smeulders; Michael D. Boot; Yvonne van der Meer (Energies, 2022)
Methanol is considered to be a viable option for reducing greenhouse gas (GHG) emissions in shipping, the second-highest emitter after road freight. However, the use of fossil methanol is insufficient to meet climate change targets, while renewable methanol is yet unavailable on a commercial scale. This paper presents a novel biorefinery concept based on biomass solvolysis to produce crude lignin oil (CLO) from forest residues, a drop-in biofuel for methanol-propelled ships, and evaluates its environmental and economic profiles. In the base scenario, CLO can achieve emission saving of 84% GHG compared to fossil alternatives, and a minimum selling price (MSP) of $821 per ton of methanol equivalent (ME), i.e., within the range of the current bio-methanol production costs. The emission of GHGs of co-produced ethanol can be reduced by 67% compared to fossil analogues. The increase of renewable electricity share to 75% is capable of shrinking emissions by 1/5 vs. the base case, while fossil methanol losses, e.g., of that in cellulose pulp, can boost emissions by 63%. Low-pressure steam use in the biomass pretreatment, as well as biorefinery capacity increase by a factor of 2.5, have the greatest potential to reduce MSP of CLO to $530 and $614 per ton of ME, respectively.